A SIGMAR1 splice-site mutation causes distal hereditary motor neuropathy. (16th June 2015) - Li, Xiaobo; Hu, Zhengmao; Liu, Lei; Xie, Yongzhi; Zhan, Yajing; Zi, Xiaohong; Wang, Junling; Wu, Lixiang; Xia, Kun; Tang, Beisha; Zhang, Ruxu
<x xml:space="preserve">Abstract</x> Objective: To identify the underlying genetic cause in a consanguineous Chinese family segregating distal hereditary motor neuropathy (dHMN) in an autosomal recessive pattern. Methods: We used whole-exome sequencing and homozygosity mapping to detect the genetic variant in 2 affected individuals of the consanguineous Chinese family with dHMN. RNA analysis of peripheral blood leukocytes and immunofluorescence and immunoblotting of stable cell lines were performed to support the pathogenicity of the identified mutation. Results: We identified 3 shared novel homozygous variants in 3 shared homozygous regions of the affected individuals. Sequencing of these 3 variants in family members revealed the c.151+1G>T mutation in SIGMAR1 gene, which located in homozygous region spanning approximately 5.3 Mb at chromosome 9p13.1-p13.3, segregated with the dHMN phenotype. The mutation causes an alternative splicing event and generates a transcript variant with an in-frame deletion of 60 base pairs in exon 1 (c.92_151del), and results in an internally shortened protein σ1R31_50del. The proteasomal inhibitor treatment increased the intracellular amount of σ1R31_50del and led to the formation of nuclear aggregates. Stable expressing σ1R31_50del induced endoplasmic reticulum stress and enhanced apoptosis. Conclusion: The homozygous c.151+1G>T mutation in SIGMAR1 caused a novel form of autosomal recessive dHMN in a Chinese consanguineous family. Endoplasmic reticulum stress may have a role in the pathogenesis of dHMN.